Human bocavirus 1 respiratory tract reactivations or reinfections in two adults, contributing to neurological deficits and death. Issue 7 (8th July 2021) - Rayamajhi Thapa, Rajita; Plentz, Annelie; Edinger, Matthias; Wolff, Daniel; Angstwurm, Klemens; Söderlund-Venermo, Maria
Abstract : Human bocavirus 1 (HBoV1) of the family Parvoviridae causes mild to life-threatening respiratory tract infections in young children, but, due to widespread immunity, it is uncommon in adults. HBoV1 reinfections or reactivations leading to casualties are rare, but might be underdiagnosed. We report two young adults, one previously healthy and one immunosuppressed, with rare diagnostic patterns of HBoV1 respiratory tract infection. Both patients exhibited very high loads of HBoV1 DNA in respiratory samples. The immunosuppressed patient was also HBoV1 DNA-positive in blood, stool and a colon biopsy, but exhibited prior HBoV1-specific high-avidity IgG and weak IgM positivity 9 months before the respiratory symptoms. Likewise, the previously healthy patient exhibited HBoV1 IgG of high avidity and very weak IgM in serum, pointing to prior immunity, but with a seroconversion in cerebrospinal fluid. This patient also showed strong HBoV2 cross-reactivity. The molecular and serological results, together with their ages, suggest that both patients exhibited unusual reinfection or reactivation of HBoV1, contributing to neurological deficits and death.